The language and stylistic peculiarities of polemical texts of Ipatii Potii and Ivan Vyshenskii in the scientific interpretation of I. Franko - Zlotnyk-Shagina Оlha (Current issues of Ukrainian linguistics: theory and practice, 2018)
In this article the language and stylistic peculiarities of works of Ivan Vyhenskii and Ipatii Potii in the scientific interpretation of Ivan Franko are investigated. The formation of Ukrainian polemic and publicistic style by authors is analyzed. The main features of the style of the writers are defined. The specific features of the main works of Ipatii Potii and Ivan Vyshenskij in the context of the epoch of Ukrainian literature Baroque in general and polemic literature partly are analyzed. It is represented the author vision of the main language and stylistic features of texts by Ipatii Potii behind Union and works of Ivan Vyshenskij against Union. It is underlined that Ivan Vyshenskii was the first writer who wrote in Ukrainian language. He founded the epoch of Baroque in the Ukrainian literature.